The Development of 3D Professional Pageflip-based Pregnancy Care E-Module - Shovrotul Khoiriyah, Ely; Sumaryanto Florentinus, Totok; Yuniastuti, Ari (Innovative Journal of Curriculum and Educational Technology, 2020)
Midwifery education has an important role in producing competent and professional midwives. Competent and professional midwife staff starts from a quality learning process. This study aimed to develop a valid and reliable 3D Pageflip Professional pregnancy care e-module. The type of research was Research and Development (R&D) research. The data collection techniques use primary data from the validation of experts (media expert and content expert). The results of this study indicated that media expert review got an average score of 3.77 (good criterion), content expert got an average score of 4.15 (good criterion) and the pregnancy care lecturer evaluation got an average score of 4.14 (good criterion). In addition, it stated that 3D Pageflip Professional pregnancy care e-module was good and deserved to be tested in the learning process. 3D Pageflip Professional pregnancy care e-module developed as an alternative to assist midwifery students in overcoming learning difficulties. Implications this article are giving the curriculum knowledge focused on learning innovations. The application of e-pregnancy care modules was easy to learn and practically accessible anywhere. To be development and innovative teaching content of education midwife and source study midwifery student so as to increase motivation and learning outcome.